DEVELOPMENT OF SOCIAL ADAPTATION OF STUDENTS IN CHILDREN (Web of Teachers: Inderscience Research, 2024)
In preschool education, a child is prepared for a comprehensive school. Among them, the development of children's speech is one of the most important. It is important for them to be able to speak freely and fully express their thoughts.